Tratamiento jurídico y psicológico para las personas procesadas por abuso sexual infantil, en la ciudad de Cartago (2021)
This document has elements such as the approach to the problem with the objective of analyzing the process of legal and psychological treatment for people prosecuted for child sexual abuse, in a penitentiary center in the city of Cartago, from a qualitative method with a descriptive scope and Narrative design, it is proposed to approach professionals linked to institutions such as ICBF, Legal Medicine, Prosecutor's Office, INPEC and Family Commissioner. Those who are responsible for dealing with cases of child sexual abuse.